The Forgotten Garden - Morton, Kate, 1976- (New York : Atria Books, 2009)
As a small girl, Nell was abandoned on a ship headed for Australia, with only a few clothes and a fairy tale book in her possession. Raised by the dockmaster and his wife, she journeys to England when she is twenty-one where she hopes to find out something about her true identity. The pieces of the puzzle are assembled following her death, after her granddaughter Cassandra discovers the forgotten garden of the book's title.
Keywords: Abandoned children -- Australia -- Fiction; English -- Australia -- Fiction; Country homes -- England -- Cornwall (County) -- Fiction; Grandmothers -- Fiction; Inheritance and succession -- Fiction; Domestic fiction